The Drugs Administration System At The Pangkajene Regency Health Service Pharmacy Installation - Mohammad Yunus; Muh Zulkifli Tahir; Sarwin Sarwin; Muhammad Alias (Public Resource Innovation Management and Excellence, 2024)
The aim of this research is to determine the drug administration system at the Pangkajene and Kepulauan District Health Service Pharmacy Installation. The research method used descriptive qualitative at the Pangkajene and Kepulauan District Health Service Pharmacy Installation Office with data collection techniques, namely observation, interviews with 11 informants and document review. The research results found that the drug administration system in the distribution function was carried out in stages from the Pangkajene and Kepulauan District Health Service Pharmacy Installation to 23 Community Health Centers and 1 Primary Hospital in La Bakkang based on the Medicine Request Sheet every month, then it would be distributed again from the Community Health Center to the local Auxiliary Health Center and Village Health Post. The function of the drug destruction sector is carried out according to the stages and minutes, as well as coordinating with related parties; The Police, Prosecutor's Office, Head of the District Food Drug Control Agency, and implementation functions are carried out in three forms; inventory control, usage. Regarding expired medicines, referring to Minister of Health Regulation Number 72 of 2016, recording and reporting are carried out by administration of availability (stock), financial administration and administration of deletion (destruction) as a form of drug management. So that the drug administration system in pharmacy installations can be better, it is recommended to improve the quality of human resources through linear continuing education programs.